(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Ordinarily, a myth is a tale or a story with a symbolicimportance. Human, non – human and super-human characters show up in myths.Furthermore the vicinity of these super-common bureaus supplies myth with a numinouscharacter. Similarly, as these characters are transcendent, they bring „awe andfear‟ up in us (Barthes 1957).